Differential expression of chemokine receptors on human IgA+ and IgG+ B cells - Johansson, C (Blackwell Science Inc, 2005)
Organ-specific lymphocyte homing is dependent on the expression of tissue-specific homing receptors and selected chemokine receptors. During the effector phase of an immune response, IgA and IgG antibody-secreting cells (ASC) are differently distributed in the body. Still, B cell expression of L-selectin and the mucosal homing receptor integrin α4β7 is not related to the isotype produced, but only to the site of antigen encounter. In this study, we examined if differences in chemokine responsiveness between IgA+ and IgG+ B cells could explain their different tissue localization. Circulating CD19+ B cells were isolated and their expression of IgA, IgG, and selected chemokine receptors was determined by flow cytometry. Few Ig+ cells expressed CCR2, CCR3, or CCR9, and there was no difference in the expression of these receptors between IgA+ and IgG+ cells. In contrast, CCR4, CCR5, and CXCR3 was expressed on significantly more IgG+ than IgA+ cells. The function of chemokine receptors on memory B cells and ASC was then tested in the transwell system. IgG+ memory cells migrated to a higher extent than IgA+ cells towards the CXCR3 ligand CXCL11/I-TAC, while there was only a small migration towards the CCR4 ligand CCL17/TARC and the CCR9 ligand CCL25/TECK. ASC migrated poorly to all chemokines tested. In conclusion, this study shows that IgG+ and IgA+ memory B cells have a differential expression of the Th1 associated chemokine receptor CXCR3, as well as of CCR4 and CCR5. In contrast, none of the studied chemokine receptors was preferentially expressed by IgA+ cells.